Determination of Thyroid Dysfunction in Pregnant Women and the Need for Universal Screening in India - V, Prabhavathi; DKV, Prasad (New Horizons in Medicine and Medical Research Vol. 5, 2022)
The current study sought to ascertain the prevalence of thyroid dysfunction and the need for universal screening in pregnant women. Three hundred and eighty pregnant women between the ages of 20 and 32, with gestational ages ranging from 8 to 36 weeks, were recruited. Chemiluminescence was used to measure the levels of free T3, free T4, and TSH in the blood. Based on the findings of the study, the pregnant women were divided into four groups: euthyroid, subclinical hypothyroid (SH), overt hypothyroid (OH), and overt hyperthyroid (OH).In this study, the mean ± SD age (in years) and BMI of all pregnant women was 23.9±3.9 and 22.9±1.6 respectively. The maternal age was statistically significant (p<0.05) in OH and overt hyperthyroidism. Similarly, women with a high BMI were more likely to develop OH than women with a normal BMI (p<0.05).Thyroid dysfunction was found to be prevalent in 18.7% of the population. Hypothyroidism was prevalent in 17.4% of the population, with the SH at 13.4% and overt hypothyroidism at 3.9 percent, but overt hyperthyroidism at 1.3 percent. TSH levels are higher with gestational age, rising from 2.72±1.85 IU/mL in the first trimester to 3.4±2.05 µIU/mL in the third trimester, with a statistically significant difference (p<0.05). Finally, it was discovered that the prevalence of elevated TSH in high-risk pregnant women was higher than in low-risk women (35.6 percent vs 5.1 percent), with a relative risk (RR) of 7.64, a 95 percent confidence interval (CI) of 4.62-12.65, and a p-value of 0.0001. However, 14 of the 51 people with SH (27.5 percent) were in the low-risk group.The results of this study found that 18.7% of pregnant women have thyroid dysfunction, emphasising the significance of screening all pregnant women for thyroid dysfunction, not just high-risk pregnant women, to avoid both maternal and foetal morbidity.